Preparation method of high-temperature self-lubricating coating of high-strength steel gun barrel piercing plug
By preparing a high-temperature self-lubricating coating on the perforated head of the high-strength steel gun barrel, the problem of premature failure of the perforated head is solved, the service life is extended, the wear resistance and friction performance is improved, and the self-lubricating effect is provided under high temperature conditions.
Patent Information
- Application Number
- CN202411822374.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The piercing head of the high-strength steel cannon pipe fails prematurely during use, which has become a key bottleneck restricting the development of high-strength steel cannon pipes.
A high-temperature self-lubricating coating preparation method is adopted to form a glaze mask coating adhered to the surface of nanocrystalline tissue through powder preparation, homogenization, plasma surfacing and high-temperature perforation treatment.
It significantly extends the service life of the head of the high-strength steel barrel perforated, and fails after 17-23 high-strength steel barrels perforated, improving wear resistance and friction performance, reducing friction wear, and providing a self-lubricating effect under high temperature conditions.
Smart Images

Figure CN119634738A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment of metal pipe perforation plugs, and in particular to a method for preparing a high-temperature self-lubricating coating on a high-strength steel gun barrel perforation plug. Background Art
[0002] With the rapid development of my country's aerospace, weapons and equipment and other cutting-edge technology fields, the demand for high-strength steel gun barrels with high dimensional accuracy, high strength characteristics and high surface quality standards is rising sharply. The requirements that existing high-strength steel gun barrels need to meet include: high strength (when the gun is firing, the gun barrel needs to withstand the effects of high-temperature, high-pressure gunpowder gas, as well as the extrusion of the barrel wall by the shells, to ensure that the barrel does not undergo permanent deformation during the firing process); high toughness (the gun barrel needs to have good toughness to prevent brittle fracture during the firing process, especially under low temperature conditions, the toughness of the material is particularly important); good heat resistance (when the gun is firing, the inner wall of the barrel will be ablated by high-temperature gunpowder gas, requiring the material to have good heat resistance to maintain the shape and dimensional stability of the barrel); good wear resistance (during long-term use, the inner wall of the gun barrel will be worn by shells and gunpowder gas, so the material is required to have good wear resistance to extend the service life of the barrel); precise size and shape (the size and shape of the gun barrel have a great influence on the shooting accuracy); good surface quality (the inner wall of the gun barrel needs to be smooth to reduce the friction and wear of the gunpowder gas on the barrel wall). Therefore, it is very necessary to carry out efficient production while ensuring the quality of high-strength steel gun barrels.
[0003] However, the core component of high-strength steel gun barrel perforation forming, the perforation plug (i.e., high-strength steel gun barrel perforation plug), always fails prematurely, becoming a key bottleneck problem restricting its development. At present, there are two main types of high-strength steel gun barrel perforation plugs used by most manufacturers: one is the perforation plug made of pure molybdenum material, but the price of this perforation plug is relatively high, which is not conducive to cost reduction and efficiency improvement for enterprises; the other is the use of conventional H13 hot-rolled die steel perforation plug, which has a relatively better cost-effectiveness, but its disadvantages include that after perforating (using) 4-8 high-strength steel gun barrels, the surface needs to be repaired before it can be used. Summary of the invention
[0004] At least in order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a method for preparing a high-temperature self-lubricating coating on a perforated plug of a high-strength steel gun barrel.
[0005] The object of the present invention is achieved through the following technical solution: A method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug, comprising the following steps: 1) Powder preparation: FeCoNiCrMn alloy is prepared by using a ceramic crucible in a vacuum medium frequency induction furnace, and FeCoNiCrMn powder is obtained by using an atomizing nozzle; 2) Powder homogenization; 3) Plasma surfacing is performed on the surface of the high-strength steel gun barrel perforation head substrate to obtain a high-strength steel gun barrel perforation head workpiece with a coating; 4) The obtained high-strength steel gun barrel perforation plug workpiece is installed on the high-strength steel gun barrel perforation equipment, and the steel pipe blank is heated to 600±1°C, and then the steel pipe blank is perforated under a constant temperature condition of 600±1°C to obtain a high-temperature self-lubricating coating with a glaze film layer attached to the surface of the high-strength steel gun barrel perforation plug.
[0006] Furthermore, the glaze film layer is attached to the surface of the nanocrystalline structure.
[0007] Preferably, the high-strength steel gun barrel perforation head base material is made of H13 hot-rolled die steel.
[0008] As the preferred solution of the present invention: Wherein, in the step 1), Fe, Co, Ni, Cr, and Mn are melted in an equal molar ratio in a ceramic crucible of a vacuum medium-frequency induction furnace to obtain a molten FeCoNiCrMn alloy liquid; the alloy liquid flows through a specific atomizing nozzle through a guide hole, and a high-pressure inert gas is sprayed from the nozzle to violently impact and shear the liquid alloy, so that the stable flow of the liquid metal is disrupted and small metal droplets are formed; under the action of surface tension, the small metal droplets begin to sphericalize and gradually solidify into FeCoNiCrMn powder; According to the alloy ratio of Fe:Co:Cr:Ni:Mn of 1:1:1:1:1, each elemental metal raw material is weighed in an equimolar ratio, and the purity of each is ≥99.99%, and is put into a crucible in a melting furnace for melting; the vacuum degree of the melting furnace is 5×10-3Mpa, and the melting time is 2-3 hours; the high-pressure inert gas is 99.999% ultra-high purity argon, and the pressure of the high-pressure inert gas is 3-5MPa.
[0009] The FeCoNiCrMn powder is prepared by the above method, which has the advantages of high production efficiency, low cost, and direct preparation of spherical powder with good sphericity. The powder prepared by the method has good sphericity, high purity, low oxygen content, and good powder fluidity. Further described, in the step 2), the FeCoNiCrMn powder in the step 1) is sieved to obtain FeCoNiCrM powder with a powder particle size of 45-105 μm, and then the sieved FeCoCrNiMn powder is poured into a V-shaped powder mixer for stirring. After the stirring is completed, the powder is placed in a drying box for drying.
[0010] The mixing time in the V-shaped mixer is 30 minutes; during the drying process, the temperature is maintained at 70-80°C for two hours.
[0011] Further description, in the step 3), the metal powder is subjected to plasma surfacing, and the plasma surfacing process parameters are: current is 180-200A, walking speed is 240-270mm / min, step length is 95-115mm, powder feeding amount is 40-55 rad / min, and coating thickness is controlled at 2-2.5mm.
[0012] In the present invention, the yield strength of the coating is ≥230 MPa, and the tensile strength is ≥485 MPa.
[0013] Further description, in the step 4), the steel pipe blank is a Q235 carbon steel block with a diameter of φ100mm; the piercing time is 30 minutes. In the piercing process, multiple Q235 carbon steel blocks in a heated state are arranged closely together (multiple Q235 carbon steel blocks are taken out of the heating furnace in turn and kept warm, the axis of the steel pipe blank is parallel to the axis of the piercing head, and the piercing process is performed) until the 30-minute time is met.
[0014] Beneficial effects: By adopting the scheme provided by the present invention, the failure time of the high-strength steel barrel perforation plug can be significantly delayed without using lubricants and with low-cost high-strength steel barrel perforation plugs, and it can be achieved that failure occurs after each perforation (use) of 17-23 high-strength steel barrels, and a technical breakthrough has been achieved in the service life of the high-strength steel barrel perforation plug made of H13 hot-rolled die steel material; and, due to the adoption of the above-mentioned technical scheme, the present invention not only has excellent wear resistance, but also has good friction performance, and effectively resists friction and wear; in the high-temperature 600°C pressure friction process, the nanocrystals formed on the subsurface have a fine-grain strengthening effect on the alloy structure, and enhance the supporting strength of the coating subsurface to the surface coating in a 600°C environment, so that the coating's deformation resistance is improved; in addition, the wear debris oxides on the coating surface undergo a sintering reaction during the friction rolling process to form a dense glaze layer, which produces a significant self-lubricating effect. In addition, the present invention has low cost and is suitable for industrial production. The heat input of plasma surfacing is small, and the heat-affected zone generated is small, which is beneficial to reducing deformation, metal deterioration and annealing. It can also ensure quality while being efficient. The turbulence of the molten pool in the surfacing is sharply weakened, making the microstructure fine and uniform, which is basically the same as the parent material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a cross-sectional TEM image of the coating sample in Example 1 (Example 1); Figure 2 3D wear scar morphologies of the coating samples in Example 1 and Comparative Example 1, (a) RT, (b) 400°C (corresponding to Comparative Example 1), (c) 600°C (corresponding to Example 1); Figure 3SEM wear scar morphologies of the coating samples in Example 1 and Comparative Example 1: (a-a1) RT, (b-b1) 400°C (corresponding to Comparative Example 1), and (c-c1) 600°C (corresponding to Example 1). DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are further described in detail below, but the present invention is not limited to these embodiments, and any improvement or substitution based on the basic spirit of the present embodiment still falls within the scope of protection required by the claims of the present invention.
[0017] Embodiment 1, a method for preparing a high-temperature self-lubricating coating on a high-strength steel gun barrel perforation plug, comprising the following steps: 1) Powder preparation: FeCoNiCrMn alloy is prepared by a vacuum medium frequency induction furnace ceramic crucible, and FeCoNiCrMn powder is obtained by an atomizing nozzle; specifically: Fe, Co, Ni, Cr, and Mn are smelted in an equal molar ratio in a vacuum medium frequency induction furnace ceramic crucible to obtain a molten FeCoNiCrMn alloy liquid; the alloy liquid flows through a specific atomizing nozzle through a guide hole, and a high-pressure inert gas is ejected from the nozzle to violently impact and shear the liquid alloy, so that the stable flow of the liquid metal is disrupted and small metal droplets are formed; under the action of surface tension, the small metal droplets begin to sphericalize and gradually solidify into FeCoNiCrMn powder; wherein the pressure of the high-pressure inert gas is 3-5MPa; 2) Powder homogenization: The FeCoNiCrMn powder in step 1) is screened to obtain FeCoNiCrM powder with a particle size of 45-105 μm, and then the screened FeCoCrNiMn powder is poured into a V-shaped powder mixer for stirring. After the stirring is completed, the powder is placed in a drying box for drying. The stirring time in the V-shaped powder mixer is 30 minutes. During the drying process, the powder is kept in an environment of 70-80° C. for two hours. 3) Plasma surfacing is performed on the surface of a high-strength steel gun barrel perforated head substrate (using H13 hot-rolled die steel) to obtain a high-strength steel gun barrel perforated head workpiece with a coating; wherein the plasma surfacing process parameters are: current of 180-200A, travel speed of 240-270mm / min, step length of 95-115mm, powder feeding amount of 40-55rad / min, and coating thickness controlled at 2-2.5mm; 4) The high-strength steel barrel perforation plug workpiece with the coating is installed on the high-strength steel barrel perforation equipment, and the steel pipe blank is heated to 600±1℃, and then the steel pipe blank is perforated under the constant temperature condition of 600±1℃ to obtain a high-temperature self-lubricating coating with a glaze film layer attached to the surface of the high-strength steel barrel perforation plug. The obtained glaze film layer is attached to the surface of the nanocrystalline structure, such as Figure 1 As shown; In this step, the steel pipe blank uses a Q235 carbon steel block with a diameter of φ100mm; the piercing time is 30 minutes. In the piercing process, multiple Q235 carbon steel blocks in a heated state are arranged closely together (multiple Q235 carbon steel blocks are taken out of the heating furnace in turn and kept warm at 1105-1130°C, the axis of the steel pipe blank is parallel to the axis of the piercing head, during the piercing process), until the 30-minute time is met. In this step, the coating of the high-strength steel barrel piercing head is subjected to specific high temperature, friction and annular pressure at the same time, which is one of the core technical points of the present invention.
[0018] The coating obtained in this embodiment was tested and combined with Figures 1 to 3 As shown, the performance test results show that the nanocrystals formed on the subsurface of the coating in this embodiment have a fine grain strengthening effect on the alloy structure, which improves the supporting strength of the subsurface of the coating on the surface coating, and improves the deformation resistance of the coating. In addition, the wear oxides on the surface of the coating undergo a sintering reaction during step 4 to form a dense glaze film layer, which produces a significant self-lubricating effect. Analysis shows that the glaze film layer is an important reason for reducing coating wear because it inhibits the direct contact between Si3N4 and the coating. Si3N4 also undergoes severe oxidation corrosion reactions at high temperatures, and silicon oxide with self-lubricating properties is formed on the surface of the coating. Although the softening of the coating structure is aggravated when treated at 600°C, the synergistic effect of the friction enamel film layer, the self-lubricating effect of silicon oxide and the sub-surface strengthening effect makes the coating have relatively better performance and service life.
[0019] Comparative Example 1, a method for preparing a high-strength steel gun barrel perforation plug high-temperature self-lubricating coating, referring to Example 1, the difference between the method and Example 1 is that step 4: installing the high-strength steel gun barrel perforation plug workpiece with the coating on the high-strength steel gun barrel perforation device, and heating the steel pipe blank to 400±1℃, and then perforating the steel pipe blank at a constant temperature of 400±1℃. The coating obtained in Comparative Example 1 was tested, and the performance test results showed that (combined with Figure 2 , 3 As shown): The morphology, peeling and other properties of the coating are obviously worse than those of the corresponding coating in Example 1.
[0020] The high-strength steel gun tube (material 35CrNiMoV, the same below) perforation plugs in Example 1 and the comparative example were used for production of high-strength steel gun tubes of DN80*6mm. The results showed that the high-strength steel gun tube perforation plug in Example 1 failed after continuous production of 21 high-strength steel gun tubes, the high-strength steel gun tube perforation plug in Comparative Example 1 failed after continuous production of 12 high-strength steel gun tubes, and the commercially available H13 hot-rolled die steel perforation plug (uncoated) failed after continuous production of 7 high-strength steel gun tubes. The high-strength steel gun tube perforation plugs in Example 1 and the comparative example were used for production of high-strength steel gun tubes of DN100*8mm. The results show that the high-strength steel gun barrel perforation plug in Example 1 failed after 18 high-strength steel gun barrels were continuously produced, the high-strength steel gun barrel perforation plug in Comparative Example 1 failed after 10 high-strength steel gun barrels were continuously produced, and the commercially available H13 hot-rolled die steel perforation plug (uncoated) failed after 4 high-strength steel gun barrels were continuously produced. When the high-strength steel gun barrel perforation plug in Example 1 was used to continuously produce ordinary carbon steel pipes with a wall thickness of 4.8 mm, 23 ordinary carbon steel pipes could be continuously produced.
[0021] By adopting the scheme provided by the present invention, the failure time of the high-strength steel barrel perforation plug can be significantly delayed without using a lubricant and with a low-cost high-strength steel barrel perforation plug, and the failure can be achieved after 17-23 high-strength steel barrels are perforated (used), and a technical breakthrough has been achieved in the service life of the high-strength steel barrel perforation plug made of H13 hot-rolled die steel material; and, due to the adoption of the above technical scheme, the present invention not only has excellent wear resistance, but also has good friction performance, and effectively resists friction and wear; in the high-temperature 600°C friction process, the nanocrystals formed on the subsurface have a fine-grain strengthening effect on the alloy structure, and the supporting strength of the coating subsurface to the surface coating in the 600°C environment is improved, so that the coating's deformation resistance is improved; in addition, the wear debris oxides on the coating surface undergo a sintering reaction during the friction rolling process to form a dense glaze film layer, which produces a significant self-lubricating effect. In addition, the present invention has low cost and is suitable for industrial production. The heat input of plasma surfacing is small, and the heat-affected zone generated is small, which is beneficial to reducing deformation, metal deterioration and annealing. It can also ensure quality while being efficient. The turbulence of the molten pool in the surfacing is sharply weakened, making the microstructure fine and uniform, which is basically the same as the parent material.
Claims
1. A method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug, characterized in that: The steps include: 1) Powder preparation: FeCoNiCrMn alloy is prepared by using a ceramic crucible in a vacuum medium frequency induction furnace, and FeCoNiCrMn powder is obtained by using an atomizing nozzle; 2) Powder homogenization; 3) Plasma surfacing is performed on the surface of the high-strength steel gun barrel perforation head substrate to obtain a high-strength steel gun barrel perforation head workpiece with a coating; 4) The coated high-strength steel gun barrel perforation plug workpiece is installed on the high-strength steel gun barrel perforation equipment, and the steel pipe blank is heated to 600±1℃, and then the steel pipe blank is perforated under a constant temperature condition of 600±1℃ to obtain a high-temperature self-lubricating coating with a glaze film layer attached to the surface of the high-strength steel gun barrel perforation plug.
2. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 1, characterized in that: The glaze film layer is attached to the surface of the nanocrystalline structure.
3. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 1, characterized in that: In the step 1), Fe, Co, Ni, Cr and Mn are melted in an equal molar ratio in a ceramic crucible of a vacuum medium frequency induction furnace to obtain a molten FeCoNiCrMn alloy liquid; the alloy liquid flows through a specific atomizing nozzle through a guide hole, and a high-pressure inert gas is sprayed from the nozzle to violently impact and shear the liquid alloy, so that the stable flow of the liquid metal is disrupted and small metal droplets are formed; under the action of surface tension, the small metal droplets begin to sphericalize and gradually solidify into FeCoNiCrMn powder.
4. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 3, characterized in that: In the step 1), the pressure of the high-pressure inert gas is 3-5 MPa.
5. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 4, characterized in that: In the step 2), the FeCoNiCrMn powder in the step 1) is sieved to obtain FeCoNiCrM powder with a particle size of 45-105 μm, and then the sieved FeCoCrNiMn powder is poured into a V-shaped powder mixer for stirring. After the stirring is completed, the powder is placed in a drying box for drying.
6. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 5, characterized in that: In step 2), the mixing time in the V-shaped powder mixer is 30 minutes; during the drying process, the temperature is maintained at 70-80° C. for two hours.
7. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to claim 6, characterized in that: In the step 3), the metal powder is subjected to plasma surfacing welding, and the plasma surfacing welding process parameters are: current of 180-200A, travel speed of 240-270mm / min, step length of 95-115mm, powder feeding amount of 40-55 rad / min, and coating thickness is controlled at 2-2.5mm.
8. The method for preparing a high-temperature self-lubricating coating on a high-strength steel gun barrel perforation plug as claimed in claim 7 is characterized in that: In the step 4), the steel pipe blank is a Q235 carbon steel block with a diameter of φ100 mm; and the piercing time is 30 minutes.
9. The method for preparing a high-temperature self-lubricating coating for a high-strength steel gun barrel perforation plug according to any one of claims 1 to 8, characterized in that: The base material of the high-strength steel gun barrel perforation head is made of H13 hot-rolled die steel.